PENGARUH KARAKTERISTIK LENDIR SERVIK SEBELUM INSEMINASI BUATAN (IB) TERHADAP KEBERHASILAN KEBUNTINGAN SAPI KOMPOSIT - Irfan Irfan; Sri Wahjuningsih; Trinil Susilawati (Jurusan Produksi Ternak, Fakultas Peternakan, Universitas Brawijaya, 2017)
The purpose of this study was to determine the effect of characteristics of cervical mucus before artificial insemination (AI) as conception rate (CR). The study materials were 112 composite cattle in estrus. Fifty five composite heifers and 57 composite cows. Samples of cervical mucus were examined for amount and consistency. The amount of the cervical mucus was studied based on its much, little and nothing of secretion the cervical mucus while the consistency was based on the thinness and thickness of the cervical mucus. The measurement of vaginal temperature was conducted by digital thermometer. The pregnancy diagnosis was performed at the 60th days post insemination. Data was analyzed by descriptive and Chi-square. Findings showed that the conception rates of composite cattle with thin, thick, and nothing secretion of cervical mucus were 66.67%, 68.00%, 35.71% on composite cows and 37.03%, 50.00%, 37.50% on composite heifers. The vaginal temperature with thin, thick, and nothing secretion of cervical mucus were 38.7±1.0 oC, 38.9±0.7 oC, 38.6±0.5 oC. It was concluded that characteristics of servical mucus before artificial insemination (AI) gave effect to conception rate. It was suggested that optimum time to artificial insemination (AI) of composite cattle was on thick and thin secretion of servical mucus. Keywords: Cervical mucus, vaginal temperature, artificial insemination (AI), composite cattle, conception rate (CR).